Serum 25-hydroxyvitamin D is associated with reduced verbal episodic memory in healthy, middle-aged and older adults - Lam, Virginie; Albrecht, Matthew; Takechi, Ryu; Prasopsang, P.; Lee, Ya Ping; Foster, Jonathan; Mamo, John (Springer Medizin, 2015)
Background - There is increasing evidence supporting an association of higher serum vitamin D concentration with better cognitive performance in older individuals. However, to date, consideration of the putative association between vitamin D and cognition has been based principally on studies investigating clinical participant samples manifesting vitamin D deficiency, particularly in older people. Moreover, relationships between vitamin D and cognition are typically not considered in the context of counter-regulatory calcium-modulating hormones or calcium homeostasis. Objective - Serum vitamin D/bioactive (ionised) calcium/parathyroid hormone homeostasis was considered in the context of cognitive performance in healthy, middle-aged and older individuals. Design - A cross-sectional sample of 179 participants between the ages of 47–84 years was recruited for this study (114 females, 65 males). Participants provided fasting blood samples for analysis of serum 25-hydroxyvitamin D levels, ionised calcium (iCa) and parathyroid hormone (PTH) and completed cognitive measures of verbal episodic learning and memory. Results - Serum 25-hydroxyvitamin D concentrations were negatively associated (with and without covariates of age, gender, depression and NART scores, iCa, and PTH) with measures of verbal episodic learning and memory, in particular with trial 5 of the Rey Auditory Verbal Learning Test (RAVLT) and long-delay free recall on the RAVLT. Conclusion - Overall, the findings from this study suggest an association between higher vitamin D status and poorer performance on verbal episodic memory in middle-aged and older individuals with normal vitamin D–calcium–PTH homeostasis. Despite requiring replication in other participant samples, this is a potentially important finding as it indicates that it may not be beneficial from a cognitive perspective to provide vitamin D supplements in individuals with already adequate vitamin D status.